Faktor Penyebab Eks Psikotik di Puskesmas Licin - Maskur Maskur; Abdul Aziz (IAI Darussalam, 2020)
Psychotic is a mental disorder that causes a person's inability to judge reality with his fantasies. The focus of the research is the factors causing the ex-psychotics at Pukesmas Licin. This research uses a descriptive analysis method with a qualitative approach. Methods of data collection by observation, interviews, and documentaries, then analyzed by interactive models. The results of the research, there is a new reality according to the version of the spikotic person, psychotic is divided into two, namely organic psychotic and functional psychotic. Ex-psychotic is a person who is declared to be recovered 70% medically with realistic testing. Ex-psychotic causes include biological factors, psychological factors, and socio-cultural factors.